Concentrated radiative cooling. (15th March 2022) - Peoples, Joseph; Hung, Yu-Wei; Li, Xiangyu; Gallagher, Daniel; Fruehe, Nathan; Pottschmidt, Mason; Breseman, Cole; Adams, Conrad; Yuksel, Anil; Braun, James; Horton, W. Travis; Ruan, Xiulin
Abstract: A fundamental limit of current radiative cooling systems is that only the top surface facing deep-space can provide the radiative cooling effect, while the bottom surface cannot. Here, we propose and experimentally demonstrate a concept of "concentrated radiative cooling" by nesting a radiative cooling system in a mid-infrared reflective trough, so that the lower surface, which does not contribute to radiative cooling in previous systems, can radiate heat to deep-space via the reflective trough. Field experiments show that the temperature drop of a radiative cooling pipe with the trough is more than double that of the standalone radiative cooling pipe. Furthermore, by integrating the concentrated radiative cooling system as a preconditioner in an air conditioning system, we predict electricity savings of > 75% in Phoenix, AZ, and > 80% in Reno, NV, for a single-story commercial building. Highlights: We develop and demonstrate a concentrated radiative cooling (CRC) device. A pipe-trough design allows radiative heat from the bottom of a pipe to deepspace. Comparing the CRC design to a standalone pipe we find 2x temperature drop. We predict a potential A/C energy savings > 75% in Reno, NV and > 80% in Phoenix, AZ.